Health conditions in retired manual labor miners and oil and gas extraction workers: National Health Interview Survey, 2007–2017. Issue 2 (26th October 2020) - Robinson, Tashina; Sussell, Aaron; Yeoman, Kristin; Retzer, Kyla; Poplin, Gerald
Abstract: Background: Within the mining industrial sector, workers in the mining and oil and gas extraction (OGE) industries have demonstrated disparities in chronic health status compared with the general working population. However, we know much less about miner and OGE worker health once retired. This study separately compares chronic illnesses in retired miners and OGE workers with all other retirees. Methods: National Health Interview Survey (NHIS) public data were analyzed for the years 2007–2017 to estimate weighted unadjusted and adjusted prevalence of selected health conditions (cancer, cardiovascular disease, high cholesterol, diabetes, hypertension, respiratory conditions, health status, and hearing loss) in retirees. Three retired worker groups (miners, OGE, and other retirees) were defined using the respondents' longest‐held industry and occupation. Results: Higher prevalence of a number of adverse health conditions was noted in miners and OGE workers when compared with all other retirees. A significantly higher adjusted prevalence of hypertension, hearing loss, functionally limiting lung problems, and fair or poor health was seen in miners over other retirees. Retired OGE workers demonstrated a significantly higher adjusted prevalence of both hearing loss and poor health status. Conclusions: Miners and OGE workers have higher morbidity during their working years, and this study demonstrates that poorer health appears to continue into retirement. These results suggest the need to expand occupational health and safety programs in the mining sector to improve the health of workers into retirement. Future studies that include more robust information on workplace exposures are needed to evaluate the long‐term health of retired workers.